Bioenrichment of conjugated linoleic acid in oil-in-water (O/W) emulsion by Niubie as a natural biocatalyst - Yusen Wu; Xiaobi Yang; Na Liu; You Chen; Jiaming Gu; Likang Qin; Song Miao (Food Bioscience, 2026)

The extract of Cirsium setosum exerts antimicrobial activities on largemouth bass infected by Aeromonas veronii via regulating inflammatory and antioxidant responses - Yuhuan Qiu; Chutong Zhang; Dekun Tang; Dasen Li; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

High Cholesterol Facilitates Ovarian Androgen Production and Contributes to the Development of Polycystic Ovary Syndrome - Yue Liu; Shourui Hu; Xiaofan Liang; Jiaming Zhang; Yiming Qin; Chunxuan Geng; Yuqing Zhang (Phenomics, 2026)

Paeoniae Radix Rubra extract inhibits largemouth bass ranavirus (LMBV) replication by suppressing inflammatory response and oxidative stress - Yang Liu; Dasen Li; Wenyan Liu; Chutong Zhang; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

Ionic liquid-modulated Co/Ni heterostructure MOF nanoflower for efficient electrochemical conversion from HMF to FDCA - Shucan Qin; Weizhen Kong; Anshuang Wu; Longmei Shi; Yuhui Ci; Yunqian Ma; Na Wang; Jiaming Mao (Journal of Environmental Chemical Engineering, 2026)

The E3 ligase RNF5 facilitates viral replication by suppressing innate immune responses in grouper - Yanqi Zhao; Xiaohui Zheng; Siting Wu; Minyao Bi; Jiaming Hu; Shaojie Liu; Jingguang Wei; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Design of a green certificate differentiated issuance mechanism based on renewable energy enterprises subsidy perspective: A case study of China - Qinliang Tan; Chaofan Shi; Jiabin Zeng; Zihan Jin; Yihong Ding; Jiaming He; Guangyu Qin (Energy Policy, 2026)

Emerging evidence of nighttime mercury oxidation driven by nitrate radical-activated heterogeneous halogen chemistry - Yan Wang; Zhenya Duan; Yi Tang; Shuxiao Wang; Zhijian Li; Qin Wang; Jiaming Fu; Qingru Wu (Journal of Hazardous Materials, 2026)

Development of a modified CaCl2·6H2O shape-stabilized composite phase change material for the greenhouse soil-cooling system - Fuyu Qin; Runhua He; Lingzhi Zhong; Tao Xu; Jiaming Gao; Ximin Lin; Yi Yang; Weitao Shao (Energy and Buildings, 2026)

Ionic liquid-derived fluorine doped high entropy metal oxides as efficient electrocatalysts for sulfion valorization - Longmei Shi; Anshuang Wu; Shengyun Xu; Jinbiao Liang; Shucan Qin; Jiaming Mao; Yanrong Liu; Yunqian Ma (Journal of Environmental Chemical Engineering, 2025)

Activation of MnOOH/γ-Bi2MoO6 composites for RhB degradation by peroxymonosulfate - Xiaoya Liang; Dan Zhao; Yanmao Dong; Shuqi Fan; Xinhao Yue; Jiaming Qin (Journal of Water Process Engineering, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Efficient separation and recycling of waste wind turbine blades through in-situ generation of peroxyacetic acid - Xinyi Xu; Jiaming Liu; Jiachun Feng; Bin Chen; Shiwen Gong; Xueer Ouyang; Changxu Qin; Gang Luo; Shicheng Zhang (Resources, Conservation and Recycling, 2025)

The comparison of anticrystallization effects of cellulose derivatives with polyvinylpyrrolidone and poloxamer on andrographolide: In vitro and in vivo characterization - Xiaoyi Zhang; Peixia Luo; Jiaming Wang; Lei Yang; Zipei Pang; Shufeng Chen; Yi Zhou; Linghao Qin (Carbohydrate Polymers, 2025)

Fabrication and saltiness enhancement of salt hollow particles by interface migration - Kailin Ye; Jiafeng Chen; Xinyu Zhang; Jiaming Qi; Zihan Qin; Jinmei Wang (Food Research International, 2025)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

Regulatory mechanisms of miR171d–SCL6 module in the rooting process of Acer rubrum L. - Huiju Li; Jiayu Yu; Jiaming Qin; Hewen Zhao; Kezhong Zhang; Wei Ge (Planta, 2024)

Southwest Boundary of Yangtze and Cathaysia Blocks: Constraints from the Luojiashan Gabbro in Yingyangguan Region, Northeastern Guangxi - Ya Qin; Zuohai Feng; Jiaming Zhu; Yonggao Huang; Jie Wu; Yun Zhou; Yunfeng Xue; Chunzeng Wang (Journal of Earth Science, 2024)

Development of a water gradient film through film and ice-glazing approach utilizing konjac glucomannan and high acyl gellan gum for enhanced preservation of frozen snakehead (Channa argus) fillets - Man Xiao; Chun Peng; Jiaming Qin; Shuangshuang Wang; Xiaohe Wu; Katsuyoshi Nishinari; Fatang Jiang (Food Hydrocolloids, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Characteristics and multi-factor mechanisms of dam construction on food web structure in cold-region rivers - Jiaming Hou; Qinghui Zeng; Peng Hu; Yunzhong Jiang; Yinglan A; Qin Yang; Baolong Zhao; Huan Liu; Zefan Yang; Xiaohui Qu (Journal of Hydrology, 2024)

Taurochenodeoxycholic acid exerts anti-viral activities upon SGIV infection via anti-inflammatory response - Fengyi Zhu; Weihua Xu; Wenji Wang; Jiaming Liao; Youhua Huang; Xiaohong Huang; Qiwei Qin (Aquaculture, 2024)

A novel fish CRADD inhibits Singapore grouper iridovirus (SGIV) infection by mediating apoptosis and modulating SGIV CARD (VP48)-caspase-2 interaction - Xin Zhang; Siting Wu; Zetian Liu; Jiaming Liao; Jingguang Wei; Qiwei Qin (Aquaculture, 2023)

Isolation and identification of a megalocytivirus strain (SKIV-TJ) from cultured spotted knifejaw (Oplegnathus punctatus) in China and its pathogenicity analysis - Jiaming Liao; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2023)

Establishment and characterization of a brain tissue cell line from spotted knifejaw ( Oplegnathus punctatus ) and its susceptibility to several fish viruses - Jiaming Liao; Xin Zhang; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Journal of Fish Diseases, 2023)
Cells are important in the study of virus isolation and identification, viral pathogenic mechanisms and antiviral immunity. The spotted knifejaw ( Oplegnathus punctatus ) is a significant farmed fish in China that has been greatly affected by diseases in recent years. In this study, a new cell line derived from the spotted knifejaw brain (SKB) was established and characterized. SKB cells multiplied well in Leibovitz's L‐15 medium supplemented with 10% fetal bovine serum at 28°C. Chromosome analysis revealed that modal chromosome number was 48 for SKB. SKB cells exhibit susceptibility to several fish viruses, such as a largemouth bass virus, red grouper nervous necrosis virus (RGNNV), infectious spleen and kidney necrosis virus (ISKNV), Singapore grouper iridovirus (SGIV) and spotted knifejaw iridovirus isolate (SKIV‐TJ), as shown by cytopathic effect and increased viral titers. Electron microscopy results showed that the cytoplasm contained a large number of vacuoles, and many virus particles existed at the edge of the vacuoles in RGNNV‐infected cells and numerous viral particles were scattered throughout the cytoplasm in both ISKNV‐ and SKIV‐TJ‐infected cells. These results suggest that SKB is an ideal tool for studying host–virus interactions and potential vaccine development.

Optimization of a compact on-site stormwater runoff treatment system: Process performance and reactor design - Yangjie Qin; Chuanting Zhou; Siqi Yu; Hongjian Pang; Jiaming Guo; Jun Wei; Libing Wang; Yunxin Xing; Ying An; Zhen Zhou (Chemosphere, 2023)

Self-healing, reprocessable, degradable, thermadapt shape memory multifunctional polymers based on dynamic imine bonds and their application in nondestructively recyclable carbon fiber composites - Xiaohong Liu; Ending Zhang; Jiaming Liu; Jingjing Qin; Mengqin Wu; Chaolong Yang; Liyan Liang (Chemical Engineering Journal, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

Effects of High-Dose of Copper Amino Acid Complex on Laying Performance, Hematological and Biochemical Parameters, Organ Index, and Histopathology in Laying Hens - Qin Zhou; Jiaming Zhu; Bing Liu; Jialing Qiu; Xintao Lu; Brian Curtin; Fei Ji; Dongyou Yu (Biological Trace Element Research, 2021)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)

Precise dating of abrupt shifts in the Asian Monsoon during the last deglaciation based on stalagmite data from Yamen Cave, Guizhou Province, China - Yan Yang; DaoXian Yuan; Hai Cheng; MeiLiang Zhang; JiaMing Qin; YuShi Lin; XiaoYan Zhu; R. Lawrence Edwards (Science China Earth Sciences, 2010)